Absence of Endocervical / Transformation Zone Component in Cervical Papanicolaou Smears in Northeastern Region of Peninsular Malaysia: Prevalence and Risk Factors - Ja’afar, Siti Mariam; Awang, Hafizuddin; Ibrahim, Raja Meriam Raja; Yasin, Zuraini; Dollah, Zawiyah (International Journal of Human and Health Sciences (IJHHS), 2020)
Background:Negative result from a satisfactory Papanicolaou (Pap) smear without endocervical cells and transformation zone (EC/TZ) components does not increase the chances of cervical cancer. However, a preparation of without EC/TZ components cannot rule out cervical cancer. Therefore, we aimed to study the factor associated with absence of EC/TZ components in Pap smear in Pasir Puteh District. Materials and Methods: A comparative cross-sectional study between groups of presence and absence of EC/TZ components in Pap smear test results was conducted among 114 samples of Pap smear screening who fulfilled study criteria in Pasir Puteh district, Kelantan state of Malaysia. Data were collected from Pap smear registry between 15th December 2019 and 15thJanuary 2020. Descriptive statistics, simple and multiple logistic regressions were used for data analysis. Results and Discussion: The prevalence of Pap smear samples with absence of EC/TZ components was 14.2% (95%CI: 0.11, 0.16). Multiple variable analysis using multiple logistic regression revealed BMI and nurses’ working duration as the significant factors associated with absence of EC/TZ components with an adjusted odds ratio (AOR) of 1.08 (95%CI:1.01, 1.16); p<0.05) and 0.85 (95%CI:0.76, 0.96; p<0.05) respectively. Conclusion:Majority of cervical cancer lesion happened in EC/TZ zone. Therefore, it is important to make sure staffs who conduct Pap smear test have received adequate training and used good sampling equipment in difficult patient to ensure the yield of the smear is satisfactory with presence of EC/TZ zone. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 178-183